How Evolution Modifies the Variability of Range Expansion. (October 2019) - Williams, Jennifer L.; Hufbauer, Ruth A.; Miller, Tom E.X.
Abstract : Eco-evolutionary theory suggests that rapid evolution can accelerate range expansion speed. In addition to average speed, recent experimental studies reveal that evolution can also influence the amount of variability across replicates of spreading populations, but in contrasting ways. Here we develop a predictive framework, drawing on ideas from population genetics and spread theory, to understand when, why, and in what direction evolution will modify the variability of range expansion. Our framework revolves around the balance of variance-generating (drift) and variance-reducing (selective) evolutionary processes, and factors that may tip this balance, including population size at the leading edge and mating system. We suggest hypotheses to clarify contrasting experimental results and highlight a way forward for studying eco-evolutionary dynamics of range expansion. Highlights: Outcomes of range expansions are variable; evolution can increase or decrease that variation. Expansion outcomes reflect a balance of variance-generating and variance-reducing evolutionary processes. Mating system and edge population size may determine whether evolution increases or decreases variance. These ideas can be tested with mathematical modeling, additional experiments, and data from natural range expansions.